Synthesis of bimetallic catalysts supported on activated carbon for fischer-tropsch reaction - Abdulrahman, Ahmed Shamil (2019)
Fischer-Tropsch Synthesis (FTS) is a process to convert a mixture of H2 and CO synthesized gas generated from biomass gasification into high quality clean fuel with low sulfur content under the existence of metal catalysts. It is believed that the incorporation of two FT active metals with high surface area and weak metal-support interaction substrate such as AC would enhance the catalytic activity and improve gasoline fraction selectivity. In this study, FT reaction was investigated in a tubular fixed bed reactor on two groups of prepared Co-Fe and Co-Ni catalysts supported by AC. The catalysts were synthesized by wet impregnation method and were characterized using high-end instrumental analysis for the morphology and physical properties of the catalysts. The incorporation of a second metal component into the catalyst has significantly modified the bimetallic catalyst properties leading to enhanced catalytic activity in FT reaction. Maximum gasoline selectivity of 63 % and 69 % were achieved on the best bimetallic catalysts namely 10Co5Fe/AC and 7Co7Ni/AC, respectively. Temperature increase from 220 °C to 300 °C enhanced gasoline selectivity from 63 % to 88 % and 69 % to 92 %. In addition, carbon monoxide (CO) conversion increased from 46 % to 72 % and 43 % to 65 % on both bimetallic 10Co5Fe/AC and 7Co7Ni/AC catalysts, respectively. On the contrary, increased reaction pressure from 1 bar to 9 bar decreased gasoline selectivity from 88 % to 22 % and 92 % to 36 % but increased CO conversion from 72 % to 97 % and 65 % to 84 % on both bimetallic 10Co5Fe/AC and 7Co7Ni/AC catalysts. The optimum reaction conditions were considered based on the maximum selectivity of gasoline which was 300 °C reaction temperature and 1 bar reaction pressure. A decrease in gasoline selectivity of 42 % and 27 % as well as a decrease in CO conversion of 56 % and 34 % was noticed on both bimetallic catalysts 10Co5Fe/AC and 7Co7Ni/AC, respectively after 64 hours on stream. The deactivation of the bimetallic catalysts was due to the deposition of carbonaceous materials on the surface of the catalysts resulting in reduction of catalyst activity. Reaction kinetics was also investigated to identify the possible reaction mechanism and kinetic parameters. The best fitted model suggested the carbide mechanism as the dominant reaction mechanism in this study. The activation energies for both bimetallic catalysts; 7Co7Ni/AC and 10Co5Fe/AC are 79 and 75 kJ/mole, respectively. The lower activation energy and increased reaction rate constant k for the bimetallic catalyst 10Co5Fe/AC suggested a faster reaction was achieved on its surface in comparison to bimetallic catalyst 7Co7Ni/AC. In conclusion, the employment of bimetallic Co-Ni and Co-Fe catalysts supported by AC in Fischer-Tropsch reaction has significantly enhanced the catalytic activity and improved gasoline selectivity. The AC generated from agricultural waste has a potential to be used as a catalyst support for the FTS reaction.